Word Forming Models of Everyday Talish Vocabulary - Alexandr Umnyashkin; Rustamkhon A. Shodiev (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
To trace the genesis and historical development of Talish affixes, we have conducted an analysis of different mechanisms of the creation of new words. The lexicological basis that we selected for our research was Talish everyday vocabulary, which contains, for historical reasons, the largest number of archaisms and includes the most ancient layers of the lexicon. We have also conducted an etymological analysis and cited examples from ancient, middle, and modern Iranian languages and several other Indo-European languages. Therefore, as our research has shown, semantic and formal changes of word-forming and form-forming affixes in Talish that take part in the formation of everyday lexicon primarily deserve close attention. The material above is a major interest in studying the history of the development of the Talish language. It also testifies to the need for a detailed and more in-depth analysis of mechanisms of word-formation in lexis linked to the names of different household items.